Emerging antimicrobial therapies for Gram-negative infections in human clinical use - Sarah M. Hickson; Emma L. Ledger; Timothy J. Wells (npj Antimicrobials and Resistance)
Abstract The growing problem of multi-drug resistance (MDR) is prevalent in Gram-negative infections, and the significant decline in antibiotic development poses a critical threat to global public health. Many emerging non-antibiotic therapies have been proposed, including phage therapy, anti-virulence agents, antimicrobial peptides, plasmapheresis, and immunotherapy options. To identify the therapies most likely to be the next immediate step in treatment for MDR Gram-negative infections, this review highlights emerging therapeutics that have either been successfully used for compassionate care or are currently undergoing clinical trials.